2008
DOI: 10.2514/1.28943
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility and Rarefaction Effects on Drag of a Spherical Particle

Abstract: A review of compressibility and rarefaction effects on spherical particle drag was conducted based on existing experimental data, theoretical limits, and direct simulation Monte Carlo method results. The data indicated a nexus point with respect to effects of Mach number and Knudsen number. In particular, it was found that a single drag coefficient (of about 1.63) is obtained for all particle conditions when the particle Reynolds number is about 45, and is independent of compressibility or rarefaction effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(116 citation statements)
references
References 29 publications
1
114
1
Order By: Relevance
“…The overall tendency of particle drag coefficient decreases with an increase of particle Reynolds number Re as shown in [10]. Before the Nexus point, Re = 45, the rarefaction effects are leading, whereas after that the compressibility effects dominate.…”
Section: Calculation Methods Ofmentioning
confidence: 89%
See 1 more Smart Citation
“…The overall tendency of particle drag coefficient decreases with an increase of particle Reynolds number Re as shown in [10]. Before the Nexus point, Re = 45, the rarefaction effects are leading, whereas after that the compressibility effects dominate.…”
Section: Calculation Methods Ofmentioning
confidence: 89%
“…The drag is the main force for particle motion, but the calculation of drag coefficient needs a modification in compressible and rarefied flows. Loth indicated that the rarefaction dominates the modifications of drag force for low slip or small particle Reynolds number flows, but the compressibility dominates the effects on drag force for high particle Reynolds number flows [10]. However, there are few investigations on two-phase vacuum plumes utilizing particle Lagrangian tracking method.…”
Section: Introductionmentioning
confidence: 99%
“…(1)) evaluation and, in turn, to assess the drag force (D) acting on the droplet, a strong deviation from the situation Re p = 1 and M p ≪ 1 is expected to occur for the §ow¦eld conditions inside the SRM and, therefore, a correction to the classical Stokes solution has to be considered. This is done employing the expression of the compressibility/high Reynolds correction provided in [15] that is a modi¦ca-tion of the CliftGauvin drag coe©cient expression [16]. Moreover, the upper and lower limits selected for the drag coe©cient in Fig.…”
Section: Ejection Of Inert Objectmentioning
confidence: 99%
“…from the standard drag model of Clift and Gauvin [25] and the compressible drag model of Loth [26]... ...... 38 [26], Parmar et al [27], Henderson [23], and Clift and Gauvin [25] Figure 33. Comparison of current data to correlations of Loth [26], Parmar et al [27], and Clift and Gauvin [25].…”
Section: Figuresmentioning
confidence: 99%